2021
DOI: 10.1136/bmjgh-2020-003743
|View full text |Cite
|
Sign up to set email alerts
|

HPV self-sampling for cervical cancer screening: a systematic review of values and preferences

Abstract: IntroductionThe WHO recommends human papillomavirus (HPV) cervical self-sampling as an additional screening method and HPV DNA testing as an effective approach for the early detection of cervical cancer for women aged ≥30 years. This systematic review assesses end user’s values and preferences related to HPV self-sampling.MethodsWe searched four electronic databases (PubMed, Cumulative Index to Nursing and Allied Health Literature, Latin American and Caribbean Health Sciences Literature and Embase) using searc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
54
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 95 publications
(99 citation statements)
references
References 87 publications
(135 reference statements)
1
54
1
Order By: Relevance
“…Some women (23.1%) preferred sampling performed by clinicians, as was previously reported in other studies [ 8 , 23 , 24 , 25 ]. In Cameroon, an earlier study explored the perceptions and preferences regarding self- versus physician-sampling in a population of women living with HIV and observed that most preferred clinician-sampling [ 26 ].…”
Section: Discussionsupporting
confidence: 61%
See 3 more Smart Citations
“…Some women (23.1%) preferred sampling performed by clinicians, as was previously reported in other studies [ 8 , 23 , 24 , 25 ]. In Cameroon, an earlier study explored the perceptions and preferences regarding self- versus physician-sampling in a population of women living with HIV and observed that most preferred clinician-sampling [ 26 ].…”
Section: Discussionsupporting
confidence: 61%
“…The reasons for preferring clinician-sampling in these studies were concerns about not doing the test correctly and the belief that health providers are more expert (95.6%), which is consistent with our findings. In the literature, women also reported having a low level of self-confidence performing self-sampling properly and providing a good quality sample for analysis [ 8 , 16 , 27 , 28 , 29 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Approximately 570 0 0 0 new cases and 310 0 0 0 deaths of CC are estimated annually worldwide ( Wang et al, 2019 ). Viral infections, especially human papillomavirus infection (HPV), which is recognized as one of the most common sexually transmitted infections worldwide, are now one of the known risk factors for CC ( Nishimura et al, 2021 ), i.e., CC is by far the most frequent HPV-related disease ( Xing et al, 2021 ). More than 200 genotypes of HPV have been identified so far; approximately 40 may infect genital areas ( Wang et al, 2015 ).…”
Section: Introductionmentioning
confidence: 99%